Development of Education and Research in Anesthesia and Intensive Care Medicine at the University Teaching Hospital in Lusaka, Zambia: A Descriptive Observational Study. (July 2017) - Janowicz, Anna; Kasole, Tuma; Measures, Emily; Langley, Meg; Goma, Fastone M.; Ismailova, Feruza; Kinnear, John A.; Bould, M. Dylan
Abstract : BACKGROUND: Data from 2006 show that the practice of anesthesia at the University Teaching Hospital in Lusaka, Zambia was underdeveloped by international standards. Not only was there inadequate provision of resources related to environment, equipment, and drugs, but also a severe shortage of staff, with no local capability to train future physician anesthetic providers. There was also no research base on which to develop the specialty. This study aimed to evaluate patient care, education and research to determine whether conditions had changed a decade later. METHODS: A mix of qualitative data and quantitative data was gathered to inform the current state of anesthesia at the University Teaching Hospital, Lusaka, Zambia. Semistructured interviews were conducted with key staff identified by purposive sampling, including staff who had worked at the hospital throughout 2006 to 2015. Further data detailing conditions in the environment were collected by reviewing relevant departmental and hospital records spanning the study period. All data were analyzed thematically, using the framework described in the 2006 study, which described patient care, education, and research related to anesthetic practice at the hospital. RESULTS: There have been positive developments in most areas of anesthetic practice, with the most striking being implementation of a postgraduate training program for physician anesthesiologists. This has increased physician anesthesia staff in Zambia 6-fold within 4 years, and created an active research stream as part of the program. Standards of monitoring and availability of drugs have improved, and anesthetic activity has expanded out of operating theaters into the rest of the hospital. A considerable increase in the number of cesarean deliveries performed under spinal anesthetic may be a marker for safer anesthetic practice. Anesthesiologists have yet to take responsibility for the management of pain. CONCLUSIONS: The establishment of international partnerships to support postgraduate training of physician anesthetists in Zambia has created a significant increase in the number of anesthesia providers and has further developed nearly all aspects of anesthetic practice. The facilitation of the training program by a global health partnership has leveraged high-level support for the project and provided opportunities for North-South and international learning. Abstract : Supplemental Digital Content is available in the text.